Changes on methane concentration after CO2 injection in a longwall gob: A case study - Hu, S.; Li, Z.; Feng, G.; Xu, Guang; Xia, T.; Jiang, H.; Zhang, Y.; Cheng, J.; Gao, Q.; Wang, Z.; Zhang, J. (2016)
Large areas of gob containing a considerable amount of methane in China are produced annually. The practice of injecting CO2 into gobs to extract methane could not only reduce the greenhouse gas emission, but also exploit clean methane resource. In this paper, an experimental apparatus was built to conduct the simulation of injecting CO2 into gob. The results show that the gob volume can be orderly divided into three zones from bottom to top: the residual coal zone (RCZ), the gas transitive zone (GTZ) and the methane enrichment zone (MEZ). The gob methane concentration exhibits an increasing trend before and after CO2 injection, and the methane concentration in the MEZ is obviously higher than that in the RCZ and GTZ. After CO2 injection, the methane concentration in RCZ decreases, while the methane concentration in the MEZ significantly increases. Meanwhile, the methane concentration in the RCZ would decrease as the total amount of CO2 injected increases and that the methane concentration in the MEZ would increase as the methane concentration in the RCZ increases. Based on the simulation results, a new in-situ technology was proposed and applied in a gob of Yiyuan mine in China to improve its methane extraction concentration by arranging a highly-located roadway in the MEZ and injecting CO2 into the GTZ. The field testing shows that this technology can increase the gob methane concentration by 22% for the highly-located roadway with an original low methane concentration of 20%-25%.